(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: The objective of this study was to determine the frequency of various endoscopic findings among patients presenting with dyspepsia in tertiary care hospital. Study Design: Cross sectional study Results: In our study, out of 240 cases of dyspeptic symptoms diagnosed clinically by a consultant, 28.33%(n=68) were between 20-40 years of age, 49.59%(n=119) were between 41-60 years and 22.08%(n=53) were between 61-80 years of age, mean ± sd was calculated as 50.30±12.96 years. 49.58%(n=119) were male and 50.42%(n=121) were females. Mean duration of symptoms was calculated as 8.71±2.34 months. Frequency of endoscopic findings among patients presenting with dyspepsia was recorded as 7.92%(n=19) had esophagitis, 5.42%(n=13) had gastritis, 4.58%(n=11) had gastric ulcer, 7.08%(n=17) had Duodenal ulcer while 75%(n=180) had functional dyspepsia. Conclusion: We concluded that on assessment of endoscopic findings among patients presenting with dyspepsia in tertiary care hospital, functional dyspepsia was found to be more frequent following by esophagitis and duodenal ulcer. The use of endoscopy may help the physicians in making guidelines to manage dyspepsia.